Application research of computer intelligent building carbon emission reduction system - Yucheng, Wang (2023)
Based on the theory of life cycle assessment, a model system for calculating the carbon emissions of building life cycle is constructed in this paper. The system includes two aspects: one is hardware, the other is software. From the function point of view, the hardware system should include four main bodies, namely, data acquisition, control center, communication and execution terminal. The software part mainly realizes the arithmetic operation, and carries on the design of the control and control interface. The carbon emissions of three types of structural systems, namely wood structure, light steel structure and reinforced concrete structure, were quantitatively calculated in the whole life cycle. The study found that the carbon emission of wooden frame was much smaller than that of the other two types of houses during the life cycle under the same performance conditions.